Liver function disorders in pregnancy: physiology or pathology? - Sielwanowska-Lasek, Wiktoria; Mądro, Agnieszka (Gastroenterology Review/Przegląd Gastroenterologiczny, 2026)
The occurrence of abnormal liver function markers in pregnancy does not always indicate pathology. Many biochemical changes, such as increased alkaline phosphatase at the end of pregnancy or decreased albumin and bilirubin, are physiological and do not cause concern for the health of the pregnant woman and child. However, due to their similarity to the symptoms of liver diseases, their interpretation is a diagnostic challenge. It is important to take into account the characteristic clinical course of individual diseases and the stage of pregnancy in which they most often occur. This article discusses liver diseases specific to pregnancy, such as hyperemesis gravidarum, HELLP syndrome, preeclampsia and eclampsia, intrahepatic cholestasis of pregnancy, and acute fatty liver disease of pregnancy, as well as diseases independent of it, such as autoimmune hepatitis (AIH), primary biliary cirrhosis, and primary sclerosing cholangitis. Although symptoms of some diseases may improve during pregnancy, there is a risk of exacerbations in AIH, especially in the perinatal period, which requires close monitoring and adjustment of immunosuppressive therapy. Differential diagnosis should also include drug-induced liver injury and viral infections. A thorough medical history and analysis of symptoms are important. Early diagnosis and rapid therapeutic action in the discussed diseases are crucial to minimise the risk of complications.